The effect of signal duration on the underwater detection thresholds of a harbor porpoise (Phocoena phocoena) for single frequency-modulated tonal signals between 0.25 and 160 kHz: - Kastelein, R.A.; Hoek, L.; Jong, C.A.F. de; Wensveen, P.J. (2010)
The underwater hearing sensitivity of a young male harbor porpoise for tonal signals of various signal durations was quantified by using a behavioral psychophysical technique. The animal was trained to respond only when it detected an acoustic signal. Fifty percent detection thresholds were obtained for tonal signals (15 frequencies between 0.25-160 kHz, durations 0.5-5000 ms depending on the frequency; 134 frequency-duration combinations in total). Detection thresholds were quantified by varying signal amplitude by the 1-up 1-down staircase method. The hearing thresholds increased when the signal duration fell below the time constant of integration. The time constants, derived from an exponential model of integration [Plomp and Bouman, J. Acoust. Soc. Am. 31, 749-758 (1959)], varied from 629 ms at 2 kHz to 39 ms at 64 kHz. The integration times of the porpoises were similar to those of other mammals including humans, even though the porpoise is a marine mammal and a hearing specialist. The results enable more accurate estimations of the distances at which porpoises can detect short-duration environmental tonal signals. The audiogram thresholds presented by Kastelein [J. Acoust. Soc. Am. 112, 334-344 (2002)], after correction for the frequency bandwidth of the FM signals, are similar to the results of the present study for signals of 1500 ms duration. Harbor porpoise hearing is more sensitive between 2 and 10 kHz, and less sensitive above 10 kHz, than formerly believed. © 2010 Acoustical Society of America.